ISSUES OF IMPROVING THE METHODOLOGY FOR CREATING GEOECOLOGICAL RESEARCH CARDS IN THE FERGANA VALLEY - Ahmatjonova Mohigul Sodiqjon qizi; Solijonova Madina Boxodir qizi; Kasimova Gulbaxor Ibroximjonovna; Shokirova Fotima Tavakkaljon qizi (Galaxy International Interdisciplinary Research Journal, 2023)
Factors (factors) that affect nature and its components; effects and pollution of nature; geoecological conditions; living conditions of the population; Ecological security, geoecalogical cards provide information about the separation of the above separately.